2020
DOI: 10.7759/cureus.11129
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Associated Anxiety and Depression in Male Hemodialysis Patients: A Cross-Sectional Study at Karachi Institute of Kidney Diseases

Abstract: Objectives Chronic kidney disease (CKD) is one of the most prevailing diseases in the world and is associated with sequelae of depression, anxiety, and sexual dysfunction. The goal of our study is to measure the prevalence of erectile dysfunction, depression, and anxiety among patients suffering from CKD and to establish a correlation between them. Methodology The research was a single-centered, descriptive cross-sectional study. All male patients present at the time of the survey were interviewed, and then ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Contrary to our findings, Serkan et al identified depression as an independent factor influencing sexual dysfunction in males with CKD 14 . Conversely, our results align with Furqan et al, who observed no significant link between depression and ED in male CKD patients at stage 5 16 . Theofilou et al even reported a negative correlation between ED and depression in CKD patients, further complicating the picture 17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Contrary to our findings, Serkan et al identified depression as an independent factor influencing sexual dysfunction in males with CKD 14 . Conversely, our results align with Furqan et al, who observed no significant link between depression and ED in male CKD patients at stage 5 16 . Theofilou et al even reported a negative correlation between ED and depression in CKD patients, further complicating the picture 17 .…”
Section: Discussionsupporting
confidence: 92%
“…GAD-7 is a screening tool for detecting anxiety. The cut-points of ≥ 5, ≥ 10 and ≥ 15 stand for mild, moderate and severe anxiety, respactively 16 , 17 .…”
Section: Methodsmentioning
confidence: 99%
“…GAD-7 is a screening tool for detecting anxiety. The cut-points of ≥ 5, ≥ 10 and ≥ 15 stands for mild, moderate and severe anxiety levels, respactively (15,16).…”
Section: Questionnairementioning
confidence: 99%
“…In addition, it is stated in the literature that coping strategies may also be associated with sexual dysfunction in the general population (Crisp et al., 2015). In the literature, the studies explored the relationships between sexual dysfunction and depression, anxiety, and quality of life in adults receiving dialysis or with chronic kidney disease (Cruz et al., 2022; Guven et al., 2018; Jarullah et al., 2020). However, the relationship between coping strategies and sexual dysfunction has not yet been explored in adults receiving HD or PD.…”
Section: Introductionmentioning
confidence: 99%